Pengembangan Traveller Game Learning Berbantuan Media Jelajah Nusantara Pada Mata Pelajaran IPS - Eko Prasetyo Utomo (SOSEARCH : Social Science Educational Research, 2021)
The purpose of this study was to determine 1) the development process of Traveler Game Learning assisted by J Exploration of the Archipelago media; 2) its implementation in the social studies subject; 3) increasing students' historical thinking skills; and 4) improving students' social skills. This research and development process refers to the Dick, Carey and Carey development procedures. The trial of the product developed was carried out at SMP Negeri Model Terpadu Bojonegoro with the sample of field trials in class VIII students totaling 30 children. The trial design used a pre-experimental design with one group pretest-posttest. The results of the validation show that the percentage of value from the learning model experts is obtained 98%, the learning tools in the form of lesson plans are 92.20%, the material is obtained 93.60%, the media is obtained 95.60%. The quality of the implementation of social studies learning, the first meeting got a percentage of 85.71%, the second meeting was 88.57%, and the third meeting was 97.14%. Overall meeting in very good category. The results of the t test on students' historical abilities showed that the t value was greater than the t table (t count = 14.89> t table value = 1.699). These results indicate that there has been an increase in students' historical thinking skills in the social studies subject after the use of the Traveler Game Learning development product assisted by the Jampang Nusantara media. Students' social skills in social studies learning have increased, namely meeting I 79.17% in good category, meeting II 83.35% in very good category, and meeting II 90.83% in very good category.